G399(P) Sturge weber syndrome type 3 masquerading as 'migraine status' at presentation. (24th May 2017) - Ahmed, MI; Jordan, P; Arora, M; Iqbal, M; Bandi, S; Prasad, M
Abstract : Introduction: Sturge-Weber Syndrome (SWS) is a rare neuro-cutaneous syndrome characterised by facial port-wine naevus and leptomeningeal angiomatosis that can be associated with neurological and ophthalmological complications. In its rare variant - SWS type 3, the clinical hallmark of facial naevus is absent which poses a diagnostic challenge. Here we present an interesting case of SWS type 3 who was admitted with prolonged severe unilateral headache mimicking migraine status. Case presentation: A 9 year old alert boy presented with a 24 hour history of vomiting and severe left temporal headache. His initial neurological examination including fundal examination was normal. Urgent CT head with contrast showed calcification in left occipital cortical and sub-cortical lobe. He had a previous admission with severe headache and prolonged seizure 3 years ago, which was managed as presumed encephalitis. On day 3 of admission, he developed a dense right sided homonymous hemianopia. Urgent MRI brain with contrast showed pial angiomatosis in the occipital and parietal lobes along with atrophy of underlying cortex consistent with the diagnosis of SWS. His headaches slowly got better but after 2 days he developed complex partial seizure and was started on regular anti-epileptic medication. On follow up after 6 weeks, he has remained seizure free with occasional mild headaches. His visual field defect has improved slightly and he is under regular neurology and ophthalmology follow-up. Discussion: SWS is a non-familial neurological disorder and has an incidence of 1:50 000 live births. SWS type 3 has only 24 cases reported in literature. SWS Type 3 is associated with a vascular malformation in the brain with no facial naevus and no glaucoma. It can have varied presentations such as seizures and as in our case headaches and visual field defects. It can only be identified through neuro-imaging with contrast, therefore it can be difficult to diagnose and does require high degree of suspicion. Learning Points: This case highlights that it is important to have high index of suspicion and low threshold for neuroimaging (with contrast) in the cases presenting with prolonged severe headaches. SWS type 3 does exist and can mimic as migraine status as the presenting feature!